Kierunki rozwoju polskiego systemu edukacji wyższej na tle procesu tworzenia europejskiego obszaru szkolnictwa wyższego - Radkowska, Jolanta; Radkowski, Krzysztof (The State and Direction of Development of Polish Higher Education in the Process of Creating the European Higher Education Area, 2007)
In the contemporary world, in this day of the fast moving processes of internationalization and globalization, the acquisition of knowledge is especially critical. In Europe the development of science and higher education is treated very seriously, the general European tendency to harmonize the systems of education is evern more explicit, and the work carried out by the so-called common European Higher Education Area named the Bologna Process. The subject under discussion is the analysis of chosen areas of activity in the framework of the Bologna Process in connection with the creation of European Higher Education Area.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1170, s. 176-186